Kata Sapaan dalam Masyarakat Tegal: Tinjauan Sosiolinguistik - Khusnul Khotimah, Leli Triana dan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2020)
The existence of different greeting words in society, shows that language has variations. Likewise, in the community of Tegal who has the Tegal dialect, they have a unique greeting that is not owned by the Javanese people who do not have the Tegal dialect. The purpose of this study is to describe the greeting words in the Tegal community, which are limited to direct greeting words. This research is a qualitative descriptive study with sociolinguistic theory. Provision of data by the method of listening with the technique of independent engage and competent listening technique is capable, then proceed with the note taking technique. Data were analyzed by translational equivalent method and pragmatic equivalent method. Presentation of data by informal methods. The results showed that the greeting words in the Tegal community which had the Tegal dialect included the greetings of kinship relations, the greetings not kinship, the greetings to village officials, and the words of religious titles. Greetings of kinship are in the form of greetings to mothers, grandparents, sisters, and siblings. The word greeting is not a kinship in the form of a greeting to boys and girls, greeting to old men and women, greeting to young men. Greetings to village officials are in the form of greetings to the lurah, shoulders, lebe, and RT heads. Greetings to people who have religious titles are in the form of greetings for hajj and religious teachers.